2019
DOI: 10.1038/s41467-019-12069-w
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cell-derived vocal fold mucosa mimics development and responses to smoke exposure

Abstract: Development of treatments for vocal dysphonia has been inhibited by lack of human vocal fold (VF) mucosa models because of difficulty in procuring VF epithelial cells, epithelial cells’ limited proliferative capacity and absence of cell lines. Here we report development of engineered VF mucosae from hiPSC, transfected via TALEN constructs for green fluorescent protein, that mimic development of VF epithelial cells in utero. Modulation of FGF signaling achieves stratified squamous epithelium from definitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 56 publications
4
57
0
2
Order By: Relevance
“…Although there was no gross in ammation observed, some level of epithelial cellular response to surface dehydration is expected. The vocal folds are covered by a non-keratinized strati ed squamous epithelium for which some aspects of development are well understood, such as embryological developmental factors and differentially expressed structural components (90,91), but a comprehensive molecular description is not available as for other epithelia like the epidermis. It is interesting that several keratinocyte developmental factors were identi ed with RNA-Seq and as a protein interaction cluster in the STRING analysis: CDSN, CNFN, CRNN, KRT80, KRTDAP, and TGM3.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no gross in ammation observed, some level of epithelial cellular response to surface dehydration is expected. The vocal folds are covered by a non-keratinized strati ed squamous epithelium for which some aspects of development are well understood, such as embryological developmental factors and differentially expressed structural components (90,91), but a comprehensive molecular description is not available as for other epithelia like the epidermis. It is interesting that several keratinocyte developmental factors were identi ed with RNA-Seq and as a protein interaction cluster in the STRING analysis: CDSN, CNFN, CRNN, KRT80, KRTDAP, and TGM3.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effect of ECVE on the human VF mucosa homeostasis, we utilized the recently developed hiPSC-derived model of human VF mucosa (15). HiPS cells were first differentiated into VF basal epithelial progenitors for 10 days and then reseeded on the top of collagen-fibroblast constructs and were let to differentiate for additional 22 days.…”
Section: Histological Alterations Of Vf Mucosae Exposed To 5% Ecvementioning
confidence: 99%
“…We have previously demonstrated that exposure of engineered VF mucosae to 5% cigarette smoke extract (CSE) leads to VF mucosa remodeling affecting predominantly the basal epithelial cell layer with downregulation of cytokeratin (K) 14 which pathologically accumulates in the luminal cells along with K13 (15). Therefore, we sought to determine whether 1-week exposure to 5% ECVE could also affect cytokeratin production and structure of the basal cellular compartment.…”
Section: Ecve Affects Compactness Of Apical Epithelial Cell Layersmentioning
confidence: 99%
See 2 more Smart Citations